Perspective Study of Critical Appraisal of Drug Promotional Literature and Clinicians Attitude towards DPL Using WHO Ethical Criteria: At aTertiary Care Centre. - Dadibhanvi, Akkamma H. (Pharmacology and Clinical Pharmacy Research, 2024)
Drug promotional literature (DPL) is a vital method used by Pharmaceutical companies for promotion of pharmaceutical products to healthcare professionals. Medical representative (MR) visits to clinician, providing DPLs  samples were  eye-catching, fascinating , even though materials were very informative accepted as it is without critical appraised, they leads to irrational prescribing practices and increasing health care cast of patients. Aim of this study to evaluate drug promotional literature by using WHO ethical criteria and perception of physician regarding DPL. The study was conducted at Al-Ameen Medical College and Hospital Vijayapura, Karnataka India. A cross sectional, observational study was carried out between the months of October 2023 and February 2024. Study was approved by institutional ethics committee and approved letter number is AMCH/AMCE 2023- 005/23. DPLs in the form of brochures, calendars, pamphlets, flip-charts, flyers, and leaflets were collected from various Out Patients Department. Clinicians were included during period DPLs samples collection. Results obtained were tabulated and analyzed using mean, frequency, percentage, descriptive statistics. Total 319 DPLs samples were collected. Total 263 DPLs samples were assessed and among them only 8 DPLs met all the WHO criteria. Present study results have found less than 50% information about therapeutic uses (45.2%).DPLs were contained drug promotion of ophthalmic condition (n-12), otorhinolaryngology(n-11) and skin diseases(n-27).Single drug promotion ( 56.3%) and FDC drug promotion (46.8%). Present study analyzed that 84.6% of clinicians had knowledge regarding WHO criteria for DPLs evaluation. 92.3% of practitioners agreed that critical appraisal of DPLs will be helpful in rational prescribing of drugs. Present study shows pharmaceutical companies are trying to stick to guidelines; however DPLs are not fulfilled completely as criteria present in OPPI code and WHO ethical criteria. Government should take legal steps to regulate pharmaceutical companies to publish DPLs according to WHO criteria.